2008
DOI: 10.1007/s11010-008-9808-3
|View full text |Cite
|
Sign up to set email alerts
|

Signal mechanism activated by erythropoietin preconditioning and remote renal preconditioning-induced cardioprotection

Abstract: It has been recently reported that release of erythropoietin could mediate the cardioprotective effects of remote renal preconditioning. However, the mechanism of erythropoietin-mediated cardioprotection in remote preconditioning is still unexplored. Therefore, the present study was designed to investigate the possible signal transduction pathway of erythropoietin-mediated cardioprotection in remote preconditioning in rats. Remote renal preconditioning was performed by four episodes of 5 min renal artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…23,24 Other underlying mechanisms may include humoral factors, such as adenosine, bradykinin, erythropoietin, d 1-opioid, and free radicals, released into the systemic circulation, which subsequently protect the remote organ. [25][26][27][28][29] Anti-Inflammatory Pathways Some studies suggested that protective effect of rIPC may be due to the beneficial anti-inflammatory or antioxidant effects, including decreased extracellular levels of noxious metabolites, such as protons and lactate. 25,30 In support of this concept, rIPC reduced neutrophil activation through expression of neutrophil CD11b and platelet neutrophil complexes.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…23,24 Other underlying mechanisms may include humoral factors, such as adenosine, bradykinin, erythropoietin, d 1-opioid, and free radicals, released into the systemic circulation, which subsequently protect the remote organ. [25][26][27][28][29] Anti-Inflammatory Pathways Some studies suggested that protective effect of rIPC may be due to the beneficial anti-inflammatory or antioxidant effects, including decreased extracellular levels of noxious metabolites, such as protons and lactate. 25,30 In support of this concept, rIPC reduced neutrophil activation through expression of neutrophil CD11b and platelet neutrophil complexes.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%
“…Our own laboratory has documented protective eŠects of ischemic preconditioning in heart 10,11) and brain. 12,13) Moreover, pharmacological preconditioning, 14,15) remote preconditioning, 16,17) and ischemic post-conditioning 18) have been documented to produce tissue-protective eŠects. In the present investigation, stress as an insult was analogous to the ischemic insult and hence, accordingly short episodes of stress were employed before sustained restrain stress, analogous to protocols employed to investigate the protective eŠects of ischemic reconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Our own laboratory has documented the protective eŠects of ischemic preconditioning in heart 10,11) and brain. 12,13) This concept has been expanded to include pharmacological preconditioning, 14,15) remote preconditioning, 16,17) and ischemic post-conditioning. 18) The concept of ischemic and pharmacological preconditioning has been extrapolated to investigate the ameliorative role of stress preconditioning on stress-induced pathological changes and there have been reports suggesting the gastroprotective eŠects of stress preconditioning on cold, alcohol, restrain, and water immersion-induced gastric lesions in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Theories include the concept that humoral substance(s) such as adenosine or bradykinin are produced by preconditioning, are released into the systemic circulation, and then protect the remote region or organ. 6,13 Other mechanistic factors proposed include erythropoietin, activation of the K ATP channel, 14,15 nitric oxide, 16 delta 1-opioid, 17,18 and free radicals. 17 Another theory is that ischemic preconditioning of 1 region or organ induces a generalized catecholamine stimulation or a sympathomimetic nerve stimulation that then induces cardioprotection.…”
Section: The Mechanism Of Remote Ischemic Preconditioningmentioning
confidence: 99%